Pengaruh GDP dan Nilai Tukar Terhadap Ekspor di Indonesia - Christianingtyas, Rachel Daffa; Kurniawan, Mahrus Lutfi Adi (Media Riset Ekonomi Pembangunan (MedREP), 2024)
Research on exports is interesting because it has many multiplier effects on the economy. If coupled with the right industrial policy, exports can create new industries that can absorb a lot of labor, identify products or commodities as competitive advantages, strengthen market share or even create "new markets" in the global scope. Increased exports can be influenced by domestic macroeconomic conditions. This study aims to analyze the influence of macroeconomics on exports in Indonesia. The study uses time-series data 1992-2023 and multiple linear regression method. Based on the regression test, it shows that GDP and exchange rate have a significant effect on the variables on exports in Indonesia, while inflation and interest rate have no significant effect on exports in Indonesia. The implementation of the research is that increasing people's purchasing power will encourage consumption growth and improve the quality of goods in export-oriented industries to encourage segmented markets.